HUBUNGAN FUNGSI PERAWATAN KELUARGA DENGAN KECEMASAN REMAJA DALAM MENGHADAPI MENARCHE DI SMP NEGERI 1 LEGOK - Siti Luthfia Awanda, (2021)
Adolescence is a phase in human life that occurs between childhood and adulthood. In women, there will be changes in the reproductive organs and the occurrence of first menstruation or called menarche. Menarche is often recognized as a scary thing in life and can cause anxiety for adolescent girls. One of the factors that cause it is because the family health function is not working well. The type of research used is quantitative research with a cross-sectional approach. The purpose of this study was to determine the relationship between the family health function and anxiety facing menarche among adolescents at SMP Negeri 1 Legok. The number of research samples was 130 people who were taken using purposive sampling technique. This study used questionnaires while in analyzing the data used chi square. The results of statistical test got p-value = 0.017, which means that there is a relation between the family health function and adolescent anxiety in facing menarche at SMP Negeri 1 Legok. Suggestions for families who have teenagers who are at the age of menarche to always provide support, either informational, emotional, instrumental, and financial support.